Perspektif Konsumen Pada Brand Image Mie Gacoan Terhadap Peningkatan Penjualan Produk - Desi Anggraini; Nafia Nur Hisnati; Anggit Dyah Kusumastuti (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The consumer's perspective on the brand image of a company's product is an important thing to pay attention to in order to help increase sales. A good brand image will create a desire to buy and consumer loyalty . Planting a brand image in the minds of consumers with good communication and labels will help provide information about a product to consumers. Thus, the role of brand image in a consumer perspective to increase sales is very necessary . Consumers will choose goods that have good quality and will also choose well-known brands or brand images. Generation Z is now in the habit of eating spicy food, one of which is noodles with various levels of taste and spiciness. Because of this consumer behavior, companies can develop various kinds of innovations. Advertisements in mass media continue to appear to increase product sales. In the process of purchasing an item, buyers will use their personal perspective to assess the quality of the item. Currently, Mie Gacoan is a spicy noodle brand that is growing rapidly, as shown by buyers' interest in long queues and a 24-hour opening system in several of its outlets. From this, we are interested in conducting research which aims to find out the consumer's perspective regarding the role of brand image in increasing product sales at the Mie Gacoan company. The method used is a literature review and a qualitative approach. Data sources used as references are research data, research reports, scientific journals and trusted official websites. The results of this research show that brand image plays a positive role in increasing product sales and is the most influential factor compared to other factors.